1987
DOI: 10.1002/pen.760271802
|View full text |Cite
|
Sign up to set email alerts
|

Injection‐molding process control—A review

Abstract: This paper reviews control strategies employed in the injection-molding process. For clarity, the controlled variables have been categorized into all-phase control, phasedependent control, and cycle-to-cycle control. All-phase control includes variables that must be monitored and controlled at all times; i.e., in all the phases. Control of variables that are triggered during a specific phase are discussed under phase-dependent control. In cycle-to-cycle control, previous data are used to predict future trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…19 Therefore, it is rational to control the process variables rather than the machine variables in order to achieve desirable and consistent part quality. As early as the late 1980s, Agrawal et al 47 suggested using "plastic variables," which are referred to as process variables here, as controlled parameters since plastic variables are the true indicators of the condition of the plastic inside the mold. The validity of the suggestion has been proven in numerous research efforts which show that the polymer melt temperature and pressure have a very strong influence on the quality of the molded part.…”
Section: Process Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Therefore, it is rational to control the process variables rather than the machine variables in order to achieve desirable and consistent part quality. As early as the late 1980s, Agrawal et al 47 suggested using "plastic variables," which are referred to as process variables here, as controlled parameters since plastic variables are the true indicators of the condition of the plastic inside the mold. The validity of the suggestion has been proven in numerous research efforts which show that the polymer melt temperature and pressure have a very strong influence on the quality of the molded part.…”
Section: Process Controlmentioning
confidence: 99%
“…As reported in Agrawal et al, 47 intelligent computation-based methods were used to model the temperature process dynamics, and advanced control strategies based on a relatively large amount of online calculation were implemented to achieve performance superior to conventional PID controllers.…”
Section: Melt Temperature Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that process parameters such as melt temperature and cavity pressure have a simpler, more direct relationship with product quality than the machine variables. [1] Others have treated the process as a linear multivariate system. [2] Attempts at intelligent or learning strategies include such studies as an expert system based on cavity pressure feedback [3], and a technique that useS an evolutionary strategy to search for the machine settings that optimize part quality.…”
Section: Introductionmentioning
confidence: 99%
“…To provide this control, feedback is needed; a method (preferably automatic) is required to provide a quantified measurement. The need for new sensor technologies has been discussed in [1] and [5], and several techniques have been investigated in [6].…”
Section: Introductionmentioning
confidence: 99%